Potentiality, Entanglement and Passion-at-a-Distance Quantum Mechanical Studies for Abner Shimony, Volume Two - Cohen, Robert S.; Horne, M.; Stachel, J.J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1997)
Potentiality, Entanglement and Passion-at-a-Distance is a book for theoretical physicists and philosophers of modern physics. It treats a puzzling and provocative aspect of recent quantum physics: the apparent interaction of certain physical events that cannot share any causal connection. These are said to be `entangled' in some way, but an explanation remains elusive. Abner Shimony - to whom the book is dedicated - and others suggest the need to revive the category of what may be seen as a metaphysical potentiality. Abner has described these events without actions to link them as `passion at a distance': not active, but passive. The discussions gathered here are written by a truly remarkable cast of scientists and philosophers and shed new light on the most profound puzzles of our times.
Protective Measurements of Two-State Vectors -- What is the Referent of a Nonpure Quantum State? -- Classical and Quantum Physical Geometry -- Borromean Entanglement of the GHZ State -- Is the Quantum State (an) Observable? -- Aiming at Describing Empirical Reality -- An Interpretation which is Appropriate for Dynamical Reduction Theories -- Einstein Podolsky Rosen Reasoning in Nonlocality Theorems -- Space-time and Separability: Problems of Identity and Individuation in Fundamental Physics -- Les recettes qui réussissent toujours -- How to Ascertain the Values of Every Member of a Set of Observables that Cannot All Have Values -- Is Quantum Mechanics a Probabilistic Theory? -- The Decision Problem for Entanglement -- Bell Inequalities with Postselection -- Action and Passion at a Distance: an essay in honour of Professor Abney Shimony -- The Relativistic EPR Argument -- The History Approach Viewed by an External Observer -- Maximal Extension of an Impossibility Theorem concerning Quantum Measurement -- Feynman Paths and Quantum Entanglement: Is There any More to the Mystery? -- Bibliography of Abner Shimony -- Index of Names -- Table of Contents to Volume One.
Keywords: Quantum physics; Philosophy and science; Elementary particles (Physics).; Quantum field theory; Natural language processing (Computer science).; Physics; Quantum Physics; Philosophy of Science; Elementary Particles, Quantum Field Theory; Natural Language Processing (NLP).; History and Philosophical Foundations of Physics